Minimally processed fresh-cut watermelons at the point-of-sale in supermarkets and hypermarkets - Gascon, Fredelyn S.; Azanza, Ma. Patricia V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
The study was conducted to determine the quality of minimally processed fresh-cut Tiger Baby watermelons at the point-of-sale (POS) in supermarkets and hypermarkets in Quezon City, Philippines. Physicochemical, sensory, and microbiological properties of fresh-cut watermelons were assessed. Supermarkets commonly prepare 5-cm base slices of watermelons while hypermarkets usually prepare 11-cm base slices. Juice leakage was found higher for watermelon packs with 5-cm base slices (6.39±1.56%) compared to packs with 11-cm base slices (0.32±0.12%). Moisture content and Aw of the 5cm-base slices were at 92.2±0.6% and 0.911±0.009 while 11-cm base slices were at 92.2±0.2% and 0.915±0.001, respectively. Overall mean values for pH, firmness, and TSS of the minimally processed watermelons from the test sources were 5.36±0.21, 18.6±6.1 mm, and 3.6±0.7oBrix. The color of the minimally processed watermelons were 24.90±1.84 (L), 35.58±2.04 (a), and 24.24±1.64 (b). Fresh-cut Tiger Baby watermelons from supermarkets were generally more acceptable than watermelons from hypermarket in terms of color, flavor, and sweetness except for crunchiness based on consumer acceptance test. In terms of microbiological quality, the overall APC for minimally processed watermelons was around 4.9±1.2 log cfu/g which was lower than the usual APC of raw ready-to-eat (RTE) food of 5.0 log cfu/g. Overall TCC (3.0±0.7 log MPN/g) was unsatisfactory based on recommended microbiological limits for RTE food in Canada. Fresh-cut minimally processed watermelons from supermarkets were established to have better quality than minimally processed watermelons from hypermarkets. This finding was mainly attributed to quality of storage conditions of whole watermelons prior to slicing or cutting and the handling of fruit during minimal processing. The study recommended the smaller cuts for minimally processed watermelons in supermarkets and hypermarkets because generally better quality was determined for smaller slices compared to larger slices.
Thesis Classification: P
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Watermelons -- Philippines